Philippines : ecology, nature protection laws and regulations handbook volume 1: strategic information and basic laws. (Philippines : International Business Publications, 2012)
"The Philippines is a newly industrialized country, with an economy anchored on agriculture but with substantial contributions from manufacturing, mining, remittances from overseas Filipinos, and service industries such as tourism, and business process outsourcing. It is also listed in the roster of the "Next eleven" economies."
Strategic and development profiles -- Important information for understanding Philippines -- Important contacts
Keywords: ENVIRONMENTAL LAW -- PHILIPPINES